2018
DOI: 10.1186/s13018-017-0709-6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic kinematics of the glenohumeral joint in shoulders with rotator cuff tears

Abstract: BackgroundNo clear trend has emerged from the literature regarding three-dimensional (3D) translations of the humerus relative to the scapula in shoulders with rotator cuff tears (RCTs). The purpose of this study was to evaluate the kinematics of RCT shoulders using 3D-to-two-dimensional (2D) model-to-image registration techniques.MethodsDynamic glenohumeral kinematics during scapular plane abduction and axial rotation were analyzed in 11 RCT patients and 10 healthy control subjects. We measured the 3D kinemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 38 publications
2
14
0
1
Order By: Relevance
“…Movements of the shoulder joint during the mentioned tasks were evaluated in this study, and the participants showed weakness of the abductor muscles when performing an abduction task (vertical reaching, task 1); however, for task 2, they demonstrated weakness of the shoulder flexor. The results of this study support previous studies, confirming that those with rotator cuff injuries demonstrate reduced shoulder flexion and abduction [12,16,19].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Movements of the shoulder joint during the mentioned tasks were evaluated in this study, and the participants showed weakness of the abductor muscles when performing an abduction task (vertical reaching, task 1); however, for task 2, they demonstrated weakness of the shoulder flexor. The results of this study support previous studies, confirming that those with rotator cuff injuries demonstrate reduced shoulder flexion and abduction [12,16,19].…”
Section: Discussionsupporting
confidence: 91%
“…The large to massive full thickness of the RCT was confirmed by magnetic resonance imaging prior to study inclusion. Moreover, X-ray imaging was used to classify severity of the disease based on Hameda's classification scheme [12]. According to this classification scheme, all patients exhibited a grade 5 condition (with humeral head collapse).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…9 For scapular plane abduction, the SHR was defined as the ratio of the difference between humeral abduction and scapular upward rotation against the scapular upward rotation. 9 The accuracy of measured values was previous evaluated, 21 and the root mean square (RMS) errors for bone were 0.16 mm for in-plane translation, 0.12 mm for out-of-plane translation, and 0.22° for rotations. The RMS error represents the standard deviation of differences between true values and measured values.…”
Section: Methodsmentioning
confidence: 99%